One-To-Many Actuation Mechanism for a 3D-Printed Anthropomorphic Hand Prosthesis - (:unkn) unknown (Springer Nature Switzerland, 2024)
Prosthetic hands become more functional and dexterous the more degrees of freedom they can control for grasping objects. Nonetheless, more degrees of freedom implies an increase in the number of actuators, cost and weight, which hinders their usability a...
Keywords: Prótesis robóticas; Impresión 3D